2017
DOI: 10.15587/2312-8372.2017.119420
|View full text |Cite
|
Sign up to set email alerts
|

Research of toxicity of chitosan-based film-forming compositions

Abstract: Із розглянутих композицій на основі хітозану та на основі аналізу характеристики лікарських відварів було обрано 20 видів для подальшого складання композиції з хітозаном 2 %. Для встановлення їх безпечного використання в плодоовочевій продукції всі зразки досліджені на токсичність та зони гемолізу. При проведенні досліджень отримані позитивні результатине було виявлено токсичності та зони гемолізу.ключові слова: композиції на основі хітозана, відвари лікарських трав, токсичність композицій, зони гемолізу на ві… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…The tested sample revealed no toxicity or hemolytic activity and inhibited B. cereus growth, with a zone diameter of 34 mm. The authors concluded that the tested preparation could serve as an excellent and safe remedy to increase the shelf life of plant-derived products [49].…”
Section: Antimicrobial Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…The tested sample revealed no toxicity or hemolytic activity and inhibited B. cereus growth, with a zone diameter of 34 mm. The authors concluded that the tested preparation could serve as an excellent and safe remedy to increase the shelf life of plant-derived products [49].…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…Antioxidative activity A, R [36,45] Antimicrobial activity against various bacterial and fungal strains A, R [32,46,47,49] Antiviral activity against herpes simplex virus type II R [50] Antineoplastic activity against HT-29 human colon cancer A [30] Effects in vivo fected the integrity of the tumor cell membranes and decreased their proliferation. In particular, extracts abundant in caffeoylquinic acids displayed the highest antineoplastic activity due to their ability to modulate the cell cycle and thus increase apoptosis.…”
Section: Effects In Vitromentioning
confidence: 99%